"SPEAKING-FOR" AND "SPEAKING-AS": PSEUDO-SURROGACY IN PHYSICIANPATIENT-COMPANION MEDICAL ENCOUNTERS ABOUT ADVANCED CANCER - Mazer, Benjamin L. (2014)
OBJECTIVE: To examine using audio-recorded encounters the extent and process of companion participation when discussing treatment choices and prognosis in the context of a life-limiting cancer diagnosis. METHODS: Qualitative analysis of transcribed outpatient visits between 17 oncologists, 49 patients with advanced cancer, and 34 companions. RESULTS: 46 qualifying companion statements were collected from a total of 28 conversations about treatment choices or prognosis. We identified a range of companion positions, from “pseudo-surrogacy” (companion speaking as if the patient were not able to speak for himself), “hearsay”, “conflation of thoughts”, “co-experiencing”, “observation as an outsider”, and “facilitation”. Statements made by companions were infrequently directly validated by the patient. CONCLUSIONS: Companions often spoke on behalf of patients during discussions of prognosis and treatment choices, even when the patient was present and capable of speaking on his or her own behalf. PRACTICE IMPLICATIONS: The conversational role of companions as well as whether the physician checks with the patient can determine whether a companion facilitates or inhibits patient autonomy and involvement. Physicians can reduce ambiguity and encourage patient participation by being aware of the when and how companions may speak on behalf of patients and by corroborating the companion's statement with the patient.